'... You can only follow my body'. Issue 2 (1st September 2017) - Hess, Sally
This article focuses on partnership, across couples and centuries. First, the married couple: my mother, a strong and dry intellect, paired with my father, water-god, all flowing passion; seventy years later, my ballroom dance instructor-parents, who teach me relationship through security born of trust, the intact self within dynamic mutuality. Last, the fraught mother–child couple. Woven throughout, a reading of Dante Alighieri's great medieval poem 'The Divine Comedy' (Dante 1949: Inferno, Cantos I, XXXI and XXXIV) serves to shade my travel from dense fear and stasis towards a future where ecstasy can be a daily event. The theme (from earth to dancer) is ground-to-body. Its variations (dancer to earth) glide across the smooth-wood dance floor. In sympathetic parallels, I trace my personal history across multiple psychological landscapes: teacher–student, leader–follower, parent–child, tender care from guide and master to the foundling pilgrim heart. The project of ballroom dancing spontaneously and consciously incarnates the isolated soul. Infernal circles of pain and sin draw the voyagers down; eventually they'll tunnel up to a new sphere of penance and ultimately of freedom. The circling dance forms evolve but never lose grateful contact with the earth. Neither myth nor literature (maybe both-and), they become a joyfully aware and centred turning on our turning planet as it fulfills its orbit in space.